Hydrogen-Terminated Two-Dimensional Germanane/Silicane Alloys as Self-Powered Photodetectors and Sensors - Roy, Pradip Kumar; Hartman, Tomáš; Šturala, Jiří; Luxa, Jan; Melle-Franco, Manuel; Sofer, Zdenek (ACS applied materials & interfaces, 2023)
2D monoelemental materials, particularly germanene and silicene (the single layer of germanium and silicon), which are the base materials for modern electronic devices demonstrated tremendous attraction for their 2D layer structure along with the tuneable electronics and optical band gap. The major shortcoming of synthesized thermodynamically very unstable layered germanene and silicene with their inclination toward oxidation was overcome by topochemical deintercalation of a Zintl phase (CaGe2, CaGe1.5Si0.5, and CaGeSi) in a protic environment. The exfoliated Ge-H, Ge0.75Si0.25H, and Ge0.5Si0.5H were successfully synthesized and employed as the active layer for photoelectrochemical photodetectors, which showed broad response (420-940 nm), unprecedented responsivity, and detectivity on the order of 168 μA W-1 and 3.45 × 108 cm Hz1/2 W-1, respectively. The sensing capability of exfoliated germanane and silicane composites was explored using electrochemical impedance spectroscopy with ultrafast response and recovery time of less than 1 s. These positive findings serve as the application of exfoliated germanene and silicene composites and can pave a new path to practical applications in efficient future devices.
Keywords: germanane and silicane; self-powered; vapor sensor; photoelectrochemical (PEC) photodetector; band bending